TANGGUNG JAWAB PENYIDIK DALAM HAL ERROR IN PERSONA - Dagani, Gamlan (REZ PUBLICA, 2019)
The writer uses library research methodology, therefore, using secondary data as the main source of the data. The issues raised in this study are basically derived from the point of view of the National Police Investigator as a law enforcement officer, what is the responsibility of the National Police investigator according to the law in the event of an error in arresting and detaining people or Error In Persona due to the negligence of the National Police investigator in carrying out his duties and obligations. The answer for the above question can be found in Indonesian criminal procedure law as regulated in Act Number.81 of 1981 concerning the Criminal Procedure Code as well as regulations relating to other criminal procedure laws such as Law Number. 2 of 2002 concerning the Republic of Indonesia National Police and the Professional Code of Ethics of the Republic of Indonesia National Police and so on. Based on the provisions mentioned above, for police investigators, the legal responsibility upon Â them is in accordance with the Professional Code of Ethics of the Indonesian National Police which expressly sanctions its members who commit violations due to negligence in carrying out their duties so as to cause harm to victims of error in persona